2008
DOI: 10.1088/0022-3727/41/5/055503
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of gas jet effect on the melt pool movements during deep penetration laser welding

Abstract: A modelling of the induced melt pool movements during iron deep penetration welding by CW Nd–YAG laser beam is developed, with the aim of studying the effect of inert gas jet on the liquid metal flow. The keyhole shape is calculated as a function of the operating parameters and the derived boundary conditions on the keyhole walls are used, by applying a solidification model, to calculate the frontiers of the assumed stationary molten pool. The vapour flow generated inside the keyhole, the surface tension and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…[23][24][25] It is interesting to note that our simulations show a similar behavior even if the influence of IB, as pointed out in Ref. 6, or the difference in the magnitude of friction force on melt induced from uprising metallic vapor jet, as pointed out in Ref.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…[23][24][25] It is interesting to note that our simulations show a similar behavior even if the influence of IB, as pointed out in Ref. 6, or the difference in the magnitude of friction force on melt induced from uprising metallic vapor jet, as pointed out in Ref.…”
Section: Resultssupporting
confidence: 83%
“…Without loss of generality, two different pressures, vacuum (0 bar) and atmospheric pressure (1 bars) are used as the ambient pressure in LW process, respectively. Both the IB effect 23 and frictions effect of vapor plume 24,25 are neglected in numerical modeling, since we intend to give an explanation of penetration depth variation that well supports most of LW processes. The process parameters used in the simulations of LW under atmospheric pressure and vacuum are the same.…”
Section: Theorymentioning
confidence: 99%
“…e friction force, which is induced on the melt-pool wall, results in a drag force expelling the flow towards the surface. e other main driving forces for the molten material in the melt-pool result from surface tension, recoil pressure, and buoyancy forces [5,85,94]. By solving a combination of the Navier-Stokes, energy conservation, and ideal gas equations, using the finite volume method, it was confirmed that using a gas jet during deep penetration laser welding results in better weld joints because the melt flow in the melt-pool is enhanced.…”
Section: Melt-pool Fluid Dynamicsmentioning
confidence: 96%
“…Amara and Fabbro [94] modeled the fluid flow in the melt-pool, considering the interaction between the vapor and the liquid and between the liquid and the air. Fabbro et al [95] showed that the escaping vapor, which is generated in the keyhole, creates friction forces, which, in turn, play an important role in fluid flow in the melt-pool.…”
Section: Melt-pool Fluid Dynamicsmentioning
confidence: 99%
“…Some numerical researches focused on the correlation between keyhole and laser-induced plasma plume were also developed to supplement the experimental observation and analysis. Amara and Fabbro [10] established a model of the induced melt pool movements during iron deep penetration welding. They found that the vapor flow generated inside the keyhole and that the surface tension as well as the recoil pressure are considered as the mechanisms producing the melt pool movements.…”
Section: Introductionmentioning
confidence: 99%